Developing Instructor Academic Competence through Scientific Article Writing and English Presentation Training - Adhi Kusumastuti; Abdurrachman Faridi; Sita Nurmasitah; Atika Atika; Imam Adi Nugroho; Lenita Eka Mayasari; Sobah Al Falah; Nuansa Kinanti Sabda Gusti (Universitas Negeri Semarang, 2025)
This community service activity aimed to improve instructors' skills in writing scientific articles and English presentations to strengthen their participation in international seminars. The main problems identified were instructors' poor ability to write articles that adhere to scientific principles and limited academic presentation skills in English. The activity was implemented in three stages: planning, implementation, and evaluation. The training methods used included guided writing, concept presentations, hands-on practice, and intensive mentoring. Evaluation was conducted through pre- and post-tests, practical performance assessments, and participant satisfaction questionnaires. The training results showed significant improvements in knowledge and skills. The average post-test score for participants increased compared to the pre-test, indicating an improved understanding of scientific writing structure and presentation techniques. Eighty-five percent of participants were able to produce complete drafts of scientific articles and demonstrated improved skills in preparing and delivering academic presentations in English, including aspects of delivery, fluency, and slide design. Furthermore, the participant satisfaction rate reached 92%, indicating that the training materials and strategies were considered relevant and beneficial for their professional development. However, this activity still has limitations, particularly related to the training duration and the variation in participants' initial abilities. Overall, this program is effective in improving the academic competency of instructors and has the potential to be replicated on a wider scale to support the continuous increase in scientific publications and international participation.